Effect of Inclusion of Dietary Mannan-oligosaccharide and a-Tocopherol in the Diet on Blood Parameters in Broiler Chicken - Sinha, Pallavi; Kumar, Sanjay; Kumar, Kaushalendra; Singh, P. K.; ., Chandramoni; Kumar, Deepak (Indian Journal of Animal Nutrition, 2017)
The present experiment was conducted to evaluate the effect of supplementing prebiotic mannan-oligosaccharide (MOS) and a-tocopherol on the blood parameters in broiler chicken. A total of 240, day-old Vencobb broiler chicks were randomly assigned to four dietary treatments having three replicates of 20 birds for 7 weeks. The chicks were fed with standard basal diet as per BIS (1992). The control group T1 was fed a basal diet. The birds in group T2 were fed control diet as in T1 + a-tocopherol @ 400 IU per kg of feed; in group T3: control diet as in T1 + mannan-oligosaccharide @ 0.4% and in group T4: control diet as in T1 + a-tocopherol @ 400 IU per kg feed + mannan-oligosaccharide @ 0.4% in feed, respectively. The values of blood haematological parameters were variable in different treatments. The glucose and total protein concentration was higher (P<0.05) in treatment groups as compared to control group. The serum ALT and ALP activity was lower (P<0.01) while that of AST was higher in treatment groups. The levels of total cholesterol, triglycerides, low density lipoprotein, high density lipoprotein and very low density lipoprotein were (P<0.05) lower in broilers fed with the dietary supplements compared to control group. Therefore, supplementation of mannan-oligosaccharide and a-tocopherol increased glucose concentration and reduced total cholesterol, triglycerides, low density lipoprotein, high density lipoprotein and very low density lipoprotein in broiler chicken.